Analisis Faktor-faktor yang Mempengaruhi Minat Berwirausaha pada Siswa Sekolah Dasar di Daerah Pedesaan - Rahmah.ZD, Nadhifa Nur; Isari, Alya; Wulandari, Tri; Rahmayani, Tria Rohana; Sholeh, Muhammad (Darul Yasin Al Sys, 2024)
Interest in entrepreneurship in elementary school students needs to be fostered from an early age, especially in rural areas which have great entrepreneurial potential. This research aims to analyze the factors that influence interest in entrepreneurship among elementary school students in rural areas. The method used is a literature test by reviewing various scientific sources such as journals, articles and books that are relevant to the research topic. The research results show that there are several factors that influence interest in entrepreneurship among elementary school students in rural areas, namely: 1) Internal factors: Personal abilities, motivation and entrepreneurial character. 2) External factors: Support from family, school and surrounding environment. Internal factors include self-confidence, the desire to be independent, and the ability to take risks and innovate. Meanwhile, external factors include support from parents and family who provide encouragement and role models in entrepreneurship, the role of teachers and the school curriculum which supports entrepreneurial education, as well as the surrounding environment which provides opportunities and resources for entrepreneurship. This research provides implications for the development of entrepreneurship education programs in elementary schools in rural areas to increase students' interest in entrepreneurship. It is hoped that the implementation of a structured and sustainable program can foster interest and entrepreneurial skills from an early age, so that students can exploit local potential and contribute to the regional economy in the future.